2014
DOI: 10.1186/s12913-014-0498-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel triage approach of child preventive health assessment: an observational study of routine registry-data

Abstract: BackgroundThe coverage of preventive health assessments for children is pivotal to the system of preventive health screening. A novel method of triage was introduced in the Preventive Youth Health Care (PYHC) system in the Netherlands with an associated shift of tasks of professionals. Doctor’s assistants carried out pre-assessments to identify children in need of follow-up assessment, whereas in the traditional approach all children would have been screened by a doctor or nurse. The accessibility and care del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…19 This has been confirmed in our study looking at referral to external services. Our results relating to referral rates to additional PCH assessments associated with the shifting of tasks from PCH physicians and nurses to PCH assistants for the age group of 10 to 11 years are in line with studies of task shifting in primary care, which found more additional assessments when nurses took over tasks from physicians, even though the number of referrals did not change.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…19 This has been confirmed in our study looking at referral to external services. Our results relating to referral rates to additional PCH assessments associated with the shifting of tasks from PCH physicians and nurses to PCH assistants for the age group of 10 to 11 years are in line with studies of task shifting in primary care, which found more additional assessments when nurses took over tasks from physicians, even though the number of referrals did not change.…”
Section: Discussionsupporting
confidence: 82%
“…19 In the triage approach, children are pre-assessed by a PCH assistant using a strict protocol which includes the completion of questionnaires by parents and teachers, and face-to-face screening (that covers areas such as growth, hearing and vision). Only children with suspected health concerns are selected by the PCH assistant for follow-up assessment by a PCH physician or nurse.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 Triage preassessments are conducted in the absence of parents, whereas the traditional health assessments are conducted with parents present. Literature claims that the early detection of health problems is more accurate when parents are present, 23,25 but this study did not find a difference in identification rates between the 2 approaches.…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study of the triage approach 16 found no change in accessibility of PCH, but significantly fewer children were referred for extra PCH assessment or for treatment by an external specialist than in a traditional approach. Further research was needed to compare the quality of care delivered by the triage approach to traditional PCH.…”
Section: What This Study Addsmentioning
confidence: 99%